A NEW DIMENSION IN ACTIVITY REPORTING AND THE PERFORMANCE OF THE ENTERPRISE – NON-FINANCIAL REPORTING - Gadau, Liana (Annals of Spiru Haret University. Economic Series, 2016)
Currently the focus is on the fact that non-financial reporting is essential for the transition to a sustainable economy which combines long-term profitability with social inclusion and protection of natural resources. Therefore, the present requirements of the European Union institutions on reporting non-financial enterprises and large groups of enterprises require that they report to both environmental and social as well as issues regarding compliance with human rights issues on combating corruption and bribery.It aims to increase the transparency and comparability among large companies. The merit and importance of non-financial reporting is that business goes beyond performance reporting financial size classical concept of performance thus completing two new dimensions, environmental and social.